Challenges in conserving ethnic culture in urban spaces: Case of Ako Dhong village (Vietnam) - Hoai Giang Dang; Ky Nam Nguyen (Cogent Social Sciences)
Most studies of ethnic heritage in Vietnam have paid much attention to those who live in remote and mountainous areas. A little attention has been given to how indigenous people in the cities have been conserving their cultural heritage. Based on a long ethnography at Ako Dhong village, an Ede community located in Buon Ma Thuot city, Central Highlands of Vietnam, from 2010 to 2020 and utilising two conceptual frameworks of political ecology and authorities versus minorities, this article seeks to analyse complicated challenges facing the community. Unlike previous investigations focusing on external influences such as state policies, migration, or religions like Protestantism and Catholicism, this research provides a multifaceted picture of internal and external factors affecting the community’s cultural heritage. We argue that the local crony capitalism represented by collusion between the state and businesses, the state’s top-down cultural approach and community rifts threaten the community’s efforts to protect cultural heritage.